Clinical and evolutionary consequences of HIV adaptation to HLA: implications for vaccine and cure - Avila-Rios, Santiago; Carlson, Jonathan M.; John, Mina; Mallal, Simon; Brumme, Zabrina L (Current Opinion in HIV and AIDS, 2019)
Purpose of review The purpose of this review is to summarize recent advances in our understanding of HIV adaptation to human leukocyte antigen (HLA)-associated immune pressures and its relevance to HIV prevention and cure research. Recent findings Recent research has confirmed that HLA is a major driver of individual and population-level HIV evolution, that HIV strains are adapting to the immunogenetic profiles of the different human ethnic groups in which they circulate, and that HIV adaptation has substantial clinical and immunologic consequences. As such, adaptation represents a major challenge to HIV prevention and cure. At the same time, there are opportunities: Studies of HIV adaptation are revealing why certain HLA alleles are protective in some populations and not others; they are identifying immunogenic viral epitopes that harbor high mutational barriers to escape, and they may help illuminate novel, vaccine-relevant HIV epitopes in regions where circulating adaptation is extensive. Elucidation of HLA-driven adapted and nonadapted viral forms in different human populations and HIV subtypes also renders ‘personalized’ immunogen selection, as a component of HIV cure strategies, conceptually feasible. Summary Though adaptation represents a major challenge to HIV prevention and cure, achieving an in-depth understanding of this phenomenon can help move the design of such strategies forward.